Produktkennzeichnung durch lokal definierte Einstellung von ferromagnetischen Eigenschaften beim Drückwalzen von metastabilen Stahlwerkstoffen - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian (36. Aachener Stahlkolloquium – Umformtechnik “Ideen Form geben“)

A flow forming process model to predict workpiece properties in AISI 304L - Arian, Bahman; Oesterwinter, Annika; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank; Kersting, Lukas; Trächtler, Ansgar (19th Int. Conference on Metal Forming 2022)

Autonomes Putten mittels datengetriebener und physikbasierter Methoden - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (Proceedings - 32. Workshop Computational Intelligence: Berlin, 1. - 2. Dezember 2022)

Learning Data-Driven PCHD Models for Control Engineering Applications* - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Validation of an Online State Estimation Concept for Microscopic Traffic Simulations◆ - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (2021 IEEE Transportation Electrification Conference & Expo (ITEC))
This paper deals with a novel method for the online fitting of a microscopic traffic simulation model to the current state of a real world traffic area. The traffic state estimation is based on limited data of different measurement sources and guarantees general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. The research is embedded in the challenge of improving the traffic by controlling the traffic light systems (TLS) of the examined area. Therefore, the current traffic state and the predicted route choices of individual road users are the matter of interest. The concept is generally transferable to any road traffic system. To give an impression of the accuracy and potential of the approach, the validation and first application results are presented.

Towards the Concept of a Digital Green Twin for a Sustainable Product Lifecycle - Michael, Jan; Grote, Eva-Maria; Pfeifer, Stefan; Rasor, Rik; Henke, Christian; Trächtler, Ansgar; Kaiser, Lydia

Connecting Energy Storages from Tool Independent, Signal-flow Oriented FMUs - Ehlert, Meik; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Kalla, Matthias; Bagaber, Bakr; Ponick, Bernd; Mertens, Axel (Proceedings of the International Conference on SMACD and 16th Conference on PRIME)

Model of a Triangular Caterpillar Drive and Analysis of Vertical Vehicle Dynamics - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Russian Engineering Research)

Subjective Evaluation of Filter- and Optimization-Based Motion Cueing Algorithms for a Hybrid Kinematics Driving Simulator - Biemelt, Patrick; Böhm, Sabrina; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the IEEE International Conference on Systems, Man, and Cybernetics (SMC))

Kraftsensitive Kalibriermethode für Industrieroboter - Schütz, Stefan; Elsner, Nikolaus; Henke, Christian; Trächtler, Ansgar (Fachtagung VDI MECHATRONIK 2021)